Using the Virtual–Representational–Abstract Approach to Support Students With Intellectual Disability in Mathematics. (December 2018) - Bouck, Emily C.; Park, Jiyoon; Shurr, Jordan; Bassette, Laura; Whorley, Abbie
Mathematics education is an important but underexplored area of research for secondary students with mild intellectual disability. In this multiple probe across behaviors replicated across two participants study, the researchers explored the effectiveness of the virtual–representational–abstract (VRA) instructional sequence to support two students' acquisition of three mathematical behaviors. Each student was able to acquire his or her three mathematical behaviors (i.e., place value, single-digit addition with regrouping, subtraction with regrouping, and single-digit multiplication) following instruction with the VRA sequence. However, each student struggled with maintenance with at least one behavior. Implications for practice relative to the VRA instructional sequence are discussed.